Novel Hydrolytic Enzymes and Protein Modelling from Marine Sedimentary Bacteria Losari Coastal, Makassar South Sulawesi, Indonesia - Anita, Anita; Natsir, Hasnah; Taba, Paulina; Ahyar , Ahmad; Soekamto, Nunuk Hariani; Permatasari, Nur Umriani; Rauf, Wahyudin; Sarlan, Sarlan; Massi, Nasrum; Sudding, Sudding; Fatmawati, Andi (Trends in Sciences, 2025)
Marine ecosystems are invaluable sources of biodiversity and unique chemical compounds, especially for the discovery of new natural products, including enzymes. Marine sediment bacteria from the Losari Coastal, Makassar City, Indonesia, show great potential for biotechnological applications due to their ability to produce enzymes with extraordinary properties such as salt tolerance, heat stability, and adaptability to extreme conditions. This study investigated the enzymatic capabilities of marine sediment bacteria isolated from the Losari Coastal, Makassar City, Indonesia, focusing on 3 enzymes: Amylase, lipase, and protease. Bacterial samples were collected from 4 coastal locations, and a comprehensive analysis of their morphological, physiological, and molecular characteristics was performed, combining 16S rRNA sequencing and protein modeling using SWISS-MODEL. This study yielded 15 bacterial isolates characterized by a gram-negative, rod-shaped morphology and distinctive, round, yellow colonies with serrated edges. Among these, 10 produced amylase, 9 produced lipases, and 10 showed protease activity; however, 2 isolates stood out because they could produce all three enzymes: amylase, lipase, and protease. The MB-SL 5 isolate showed 97.82% similarity to Shewanella algae strain DW01, and the MB-SL 6 isolate had 90.53% similarity to Vibrio alginolyticus NBRC 15630 strain, with predicted protein structure code A0A3M5GRJ4_1 A. These findings highlight the significant biotechnological potential of marine sediment bacteria from the Losari Coastal producing hydrolytic enzymes for industrial applications, which opens new avenues for the development of new biocatalysts. HIGHLIGHTS Pioneering Exploration of the Ecosystem as an Optimal Source for Enzyme-Producing Bacteria: This study represents the 1st comprehensive investigation of marine sedimentary bacteria from the unique Losari Coastal ecosystem in Makassar City, Indonesia, revealing previously uncharacterized enzymatic capabilities. Multi-Enzyme Production in Indigenous Bacterial Strains: The discovery of local bacterial strains capable of producing all three industrially valuable enzymes (amylase, lipase, and protease) simultaneously represents a significant advancement in biocatalyst research. Integration of Advanced Structural Prediction: The novel combination of 16S rRNA sequencing with SWISS-MODEL protein modeling provides unprecedented structural insights into the enzymes produced by these marine bacteria. Identification of Specific Protein Structure Codes: The research uniquely assigns specific protein structure codes (A0A3M5GRJ41.A protein) to the enzymes produced by algae and V. alginolyticus, enabling precise characterization for future applications. Enzyme Properties from a Tropical Coastal Source: The study reveals the unexpected presence of enzyme properties (salt tolerance, temperature stability) in bacteria from a tropical coastal environment rather than traditional extreme habitats, expanding our understanding of where such valuable biocatalysts can be sourced. GRAPHICAL ABSTRACT